Polymerizable liquid crystal composition, polarizing film, polarizing film sheet, circularly polarizing plate, and display device
Patent Information
- Application Number
- CN202280008092.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-28
- Filing Date
- 2022-01-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-01-17
AI Technical Summary
[0030] According to the present invention, a polymeric liquid crystal composition suitable for forming a polarizing film with excellent yellowing suppression effect can be provided.
Smart Images

Figure BDA0004279819970000071 
Figure BDA0004279819970000081 
Figure BDA0004279819970000091
Abstract
Description
Technical Field
[0001] The present invention relates to a polymeric liquid crystal composition, a polarizing film formed from a cured film of the aforementioned polymeric liquid crystal composition, a polarizing film sheet comprising the aforementioned polarizing film and a circular polarizing plate, and a display device. Background Technology
[0002] Previously, in various image display panels such as liquid crystal display panels and organic electroluminescent (OLED) display panels, polarizing plates were used and bonded to image display elements such as liquid crystal cells and OLED display elements. In recent years, there has been a continuous demand for thinner displays such as image display panels, and further thinning is required for polarizing plates and polarizers, which are one of their constituent elements. To address such demands, for example, a thin coated polarizing film formed from a polymerizable liquid crystal compound and a compound that displays dichroism has been proposed (Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-008683 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] In recent years, with the expansion of applications of thin polarizing plates, there has been a demand for the development of polarizing films with further improved light resistance. Among these, the inventors of this application have discovered that polarizing films yellow over time, which can cause problems such as hindering the blue emission of organic light-emitting diodes (OLEDs).
[0008] Therefore, the object of the present invention is to provide a polymeric liquid crystal composition suitable for forming a polarizing film with excellent yellowing suppression effect.
[0009] Methods for solving problems
[0010] The inventors of this application conducted in-depth research to solve the aforementioned problems, resulting in the completion of this invention. Specifically, this invention provides the following preferred embodiments.
[0011] [1] A polymerizable liquid crystal composition comprising a polymerizable liquid crystal compound, an organic dichroic pigment, and a sulfur-based antioxidant.
[0012] The aforementioned polymerizable liquid crystal compound has at least one free radical polymerizable group.
[0013] The aforementioned sulfur-based antioxidants have aromatic ring structures, thiols, or thioether structures.
[0014] [2] The polymeric liquid crystal composition as described in [1] above, wherein the sulfur-based antioxidant is at least one selected from the group consisting of thiols having aromatic rings, thioethers having aromatic rings, and cyclic thioethers having aromatic rings.
[0015] [3] The polymeric liquid crystal composition as described in [1] or [2] above, wherein the polymeric liquid crystal compound is a liquid crystal compound exhibiting smectic liquid crystal properties.
[0016] [4] The polymeric liquid crystal composition as described in any one of [1] to [3] above, wherein the organic dichroic pigment is an azo pigment.
[0017] [5] The polymeric liquid crystal composition as described in any one of [1] to [4] above, wherein the organic dichroic pigment has an aromatic ring structure.
[0018] [6] The polymeric liquid crystal composition as described in any one of [1] to [5] above, wherein the content of the sulfur-based antioxidant is 0.1 to 3 parts by mass relative to 100 parts by mass of the polymeric liquid crystal compound.
[0019] [7] A polarizing film formed from a cured film of the polymeric liquid crystal composition described in any one of [1] to [6] above.
[0020] [8] The polarizing film described above [7] shows a Bragg peak in X-ray diffraction measurements.
[0021] [9] The polarizing film described in [7] or [8] above has a thickness in the range of 0.5 to 4 μm.
[0022]
[10] A polarizing film comprising any one of the polarizing films and transparent films described in any one of [7] to [9] above.
[0023]
[11] A circular polarizer, comprising the polarizing film and phase difference film described in any one of [7] to [9] above.
[0024]
[12] As described in
[11] above, the circular polarizer, wherein the phase difference film satisfies equations (1) and (2):
[0025] 100nm≤Re(550)≤150nm (1)
[0026] Re(450) / Re(550)<1 (2)
[0027] [In the formula, Re(λ) represents the frontal phase difference of light relative to wavelength λnm].
[0028]
[13] A display device comprising any one of the polarizing film described in any one of [7] to [9] above, the polarizing film sheet described in
[10] above, or the circular polarizing plate described in
[11] or
[12] above.
[0029] Invention Effects
[0030] According to the present invention, a polymeric liquid crystal composition suitable for forming a polarizing film with excellent yellowing suppression effect can be provided. Detailed Implementation
[0031] The embodiments of the present invention will now be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the spirit of the invention.
[0032] <Polymerizable Liquid Crystal Composition>
[0033] The polymerizable liquid crystal composition of the present invention comprises a polymerizable liquid crystal compound having at least one free radical polymerizable group. The aforementioned polymerizable liquid crystal compound is a compound having at least one free radical polymerizable group and exhibiting liquid crystal properties. The free radical polymerizable group can be any functional group capable of undergoing a free radical polymerization reaction; for example, groups having carbon-carbon unsaturated double bonds can be included, specifically vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, etc. Acryloyloxy, methacryloyloxy, and vinyloxy are preferred, acryloyloxy and methacryloyloxy are more preferred, and acryloyloxy is even more preferred.
[0034] In this invention, the polymerizable liquid crystal compound is preferably a liquid crystal compound exhibiting a smectic liquid crystal phase. By using a polymerizable liquid crystal compound exhibiting a smectic liquid crystal phase, a polarizing film with high orientation order can be formed. From the viewpoint of achieving higher orientation order, the liquid crystal state exhibited by the polymerizable liquid crystal compound is more preferably a higher-order smectic phase (higher-order smectic liquid crystal state). Here, the term "higher-order smectic phase" refers to smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase, and smectic L phase, among which smectic B phase, smectic F phase, and smectic I phase are more preferred. The liquid crystal property can be a thermotropic liquid crystal or a lyotropic liquid crystal; from the viewpoint of enabling dense film thickness control, a thermotropic liquid crystal is preferred. Furthermore, the polymerizable liquid crystal compound can be a monomer or an oligomer or polymer formed by the polymerization of polymeric groups.
[0035] As a polymerizable liquid crystal compound, any liquid crystal compound having at least one free radical polymerizable group is acceptable, and there is no particular limitation; known polymerizable liquid crystal compounds can be used. For example, a compound represented by the following formula (A) (hereinafter also referred to as "polymerizable liquid crystal compound (A)") can be cited as such a polymerizable liquid crystal compound.
[0036] U 1 -V 1 -W 1 -(X 1 -Y 1 ) n -X 2 -W 2 -V 2 -U 2 (A)
[0037] In formula (A),
[0038] X 1 and X 2 Each of these groups independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atom in the divalent aromatic group or divalent alicyclic hydrocarbon group can be substituted by a halogen atom, an alkyl group with 1 to 4 carbon atoms, a fluoroalkyl group with 1 to 4 carbon atoms, an alkoxy group with 1 to 4 carbon atoms, a cyano group, or a nitro group. The carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group can be replaced by oxygen atoms, sulfur atoms, or nitrogen atoms. Wherein, X 1 and X 2 At least one of them is 1,4-phenylene or cyclohexane-1,4-diyl, which may have substituents.
[0039] Y 1 It is a single bond or a divalent linker.
[0040] When n is 1 to 3, or n is 2 or more, multiple X 1 They can be the same or different. X 2 Can be used with multiple X 1 Any one or all of them can be the same, or they can be different. Furthermore, when n is 2 or more, multiple Ys... 1 They can be the same or different. From the viewpoint of liquid crystal properties, n is preferably 2 or more.
[0041] U 1 It represents a hydrogen atom or a polymeric group.
[0042] U 2 It indicates a polymerizable group.
[0043] W 1 and W 2 Each group is a single bond or a divalent linker, independent of the others.
[0044] V 1 and V 2 Each of these groups independently represents an alkane diene with 1 to 20 carbon atoms that may have substituents, wherein the -CH2- group constituting the alkane diene can be replaced by -O-, -CO-, -S-, or NH-.
[0045] In polymeric liquid crystal compound (A), X 1 and X 2 Independently preferred are 1,4-phenylene, which may have substituents, or cyclohexane-1,4-diyl, which may have substituents, X 1 and X 2 At least one of them is a 1,4-phenylene that may have a substituent, or a cyclohexane-1,4-diyl that may have a substituent, preferably trans-cyclohexane-1,4-diyl. Examples of substituents optionally present in the 1,4-phenylene that may have a substituent, or the cyclohexane-1,4-diyl that may have a substituent, include alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl, and butyl, cyano groups, and halogen atoms such as chlorine and fluorine atoms. Unsubstituted is preferred.
[0046] Furthermore, regarding the polymerizable liquid crystal compound (A), from the viewpoint of easily exhibiting smectic liquid crystal properties, it is preferable that the portion represented by formula (A1) in formula (A) [hereinafter also referred to as the partial structure (A1)] is an asymmetric structure.
[0047] -(X 1 -Y 1 ) n -X 2 -(A1)
[0048] [In the formula, X] 1 Y 1 X 2 And n each have the same meaning as described above.
[0049] As a polymeric liquid crystal compound (A) with a partially asymmetric structure (A1), examples include those with n=1 and 1 X. 1 With X 2 These are polymeric liquid crystal compounds with different structures from each other. Additionally, examples include: n = 2 and 2 Y... 1 For the same structure, and 2 X 1 For the same structure and 1 X 2 To be with these two X 1 Polymerizable liquid crystal compounds with different structures; n is 2 and there are 2 Y atoms 1 For the same structure, and 2 X 1 In and W 1 bonded X 1 To be with another X1 and X 2 Different structures, and another X 1 With X 2 These are polymeric liquid crystal compounds with identical structures. Furthermore, examples include: n = 3 and 3 Y atoms. 1 They have the same structure and 3 X's 1 and 1 X 2 Any one of them is a polymeric liquid crystal compound with a structure different from the other three.
[0050] Y 1 Preferred bonds include -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bonds, -N=N-, and -CR. a =CR b -、-C≡C-、-CR a =N- or -CO-NR a -. R a and R b Each of the following groups independently represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms. 1 More preferably, it is -CH2CH2-, -COO-, or a single bond, and multiple Y bonds exist. 1 In the case of X 2 Bonded Y 1 More preferably, it is -CH2CH2- or -CH2O-. X 1 and X 2 When all structures are identical, it is preferable to have two or more Y atoms with different bonding methods. 1 There exist multiple Ys with different bonding methods. 1 In this case, it becomes an asymmetric structure, and therefore tends to exhibit smectic liquid crystal properties.
[0051] U 2 It is a polymerizable group. U 1 It can be a hydrogen atom or a polymeric group, preferably a polymeric group. U 1 and U 2 Any one of them is a free radical polymerizable group, preferably U. 1 and U 2 All are polymerizable groups, and more preferably, all are free radical polymerizable groups. Examples of polymerizable groups include the same free radical polymerizable groups exemplified above as polymerizable groups present in polymerizable liquid crystal compounds. 1 The polymerizable group represented by U 2 The polymerizable groups represented may be different from each other, but are preferably of the same kind, preferably U. 1 and U 2At least one of them is (meth)acryloyloxy, more preferably both are (meth)acryloyl groups. In addition, the polymerizable group can be in a polymerized state or in an unpolymerized state, preferably in an unpolymerized state.
[0052] As V 1 and V 2 Examples of alkane diyl groups include methylene, ethylene, propane-1,3-diyl, butane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, decane-1,10-diyl, tetradecane-1,14-diyl, and eicosane-1,20-diyl. 1 and V 2 Preferably, it is an alkane diester with 2 to 12 carbon atoms, and more preferably an alkane diester with 6 to 12 carbon atoms.
[0053] Examples of substituents that may be optionally present in the alkane diene include cyano groups and halogen atoms. The alkane diene is preferably unsubstituted, and more preferably an unsubstituted straight-chain alkane diene.
[0054] As W 1 and W 2 Each of these components is preferably a single bond, -O-, -S-, -COO-, or -OCOO-, and more preferably a single bond or -O-.
[0055] As a structure that readily exhibits smectic liquid crystal properties, a molecular structure with asymmetry in its molecular structure is preferred. Specifically, the polymeric liquid crystal compound (A) is more preferably a polymeric liquid crystal compound having partial structures (Aa) to (Ai) below and exhibiting smectic liquid crystal properties. From the viewpoint of readily exhibiting higher-order smectic liquid crystal properties, partial structures having (Aa), (Ab), or (Ac) are more preferred. It should be noted that in (Aa) to (Ai) below, * indicates a connecting bond (single bond).
[0056] [Chemical Formula 1]
[0057]
[0058] Examples of polymerizable liquid crystal compounds (A) include those represented by formulas (A-1) to (A-25). When the polymerizable liquid crystal compound (A) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably the trans form.
[0059] [Chemical Formula 2]
[0060]
[0061] [Chemical Formula 3]
[0062]
[0063] [Chemical Formula 4]
[0064]
[0065] Among these, at least one is preferably selected from the group consisting of compounds represented by formulas (A-2), (A-3), (A-4), (A-5), (A-6), (A-7), (A-8), (A-13), (A-14), (A-15), (A-16), and (A-17). As the polymerizable liquid crystal compound (A), one may be used alone, or two or more may be used in combination.
[0066] Polymerizable liquid crystal compound (A) can be manufactured, for example, by known methods described in Lub et al., Recl.Trav.Chim.Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156.
[0067] The polymeric liquid crystal composition of the present invention may also contain other polymeric liquid crystal compounds besides polymeric liquid crystal compound (A), as long as it does not impair the effects of the present invention. From the viewpoint of obtaining a polarizing film with high orientation order, the proportion of polymeric liquid crystal compound (A) relative to the total mass of all polymeric liquid crystal compounds in the polymeric liquid crystal composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. By combining multiple polymeric liquid crystal compounds, liquid crystal properties can sometimes be temporarily maintained even at temperatures below the liquid crystal phase transition temperature.
[0068] Regarding the content of the polymeric liquid crystal compound in the polymeric liquid crystal composition of the present invention, it is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and even more preferably 70 to 99% by mass, relative to the solid component of the polymeric liquid crystal composition. When the content of the polymeric liquid crystal compound is within the above range, there is a tendency for the orientation of the polymeric liquid crystal compound to be improved.
[0069] In this specification, solid components refer to the total amount of components obtained after removing volatile components such as solvents from the polymeric liquid crystal composition.
[0070] The polymerizable liquid crystal composition of the present invention comprises an organic dichroic pigment. Here, an organic dichroic pigment refers to an organic pigment having the property that the absorbance along the long axis of the molecule differs from that along the short axis. The organic dichroic pigment used in the present invention is not particularly limited as long as it possesses the above-mentioned properties; it can be a dye or a pigment. Two or more dyes or pigments can be used in combination, or dyes and pigments can be used in combination. Furthermore, the dichroic pigment can be polymerizable and can be liquid crystallizable.
[0071] As an organic dichroic pigment, it is preferably found to have a maximum absorption wavelength (λ) in the range of 300–700 nm. MAX ).
[0072] Examples of such organic dichroic pigments include acridine pigments, oxazine pigments, anthocyanins, naphthalene pigments, azo pigments, and anthraquinone pigments.
[0073] Examples of azo dyes include monoazo dyes, diazo dyes, triazo dyes, tetraazo dyes, and pizo dyes, with diazo dyes and triazo dyes being preferred. For example, compounds represented by formula (I) (hereinafter also referred to as "compound (I)") can be cited.
[0074] K 1 (-N=NK) 2 ) p -N=NK 3 (I)
[0075] In formula (I), K 1 and K 3 Each can be represented independently as a phenyl group that may have a substituent, a naphthyl group that may have a substituent, a phenyl benzoate group that may have a substituent, or a monovalent heterocyclic group that may have a substituent. K 2 This indicates a substituent-containing p-phenylene, a substituent-containing naphth-1,4-diyl, a substituent-containing 4,4'-pyridylene, or a substituent-containing divalent heterocyclic group. p represents an integer from 0 to 4. When p is an integer greater than 2, multiple K... 2 They can be the same or different. Within the visible light absorption range, the -N=N- bond can be replaced by -C=C-, -COO-, -NHCO-, or -N=CH- bonds.
[0076] Examples of monovalent heterocyclic groups include those obtained by removing one hydrogen atom from heterocyclic compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of divalent heterocyclic groups include those obtained by removing two hydrogen atoms from the aforementioned heterocyclic compounds.
[0077] As K1 and K 3 The phenyl, naphthyl, phenyl benzoate ester group and monovalent heterocyclic group, as well as K 2 The p-phenylene, naphthyl-1,4-diyl, 4,4'-indene, and divalent heterocyclic groups may optionally contain substituents, such as: alkyl groups with 1 to 20 carbon atoms; alkyl groups with 1 to 20 carbon atoms that have polymerizable groups; alkenyl groups with 1 to 4 carbon atoms; alkoxy groups with 1 to 20 carbon atoms, such as methoxy, ethoxy, and butoxy; alkoxy groups with 1 to 20 carbon atoms that have polymerizable groups; fluoroalkyl groups with 1 to 4 carbon atoms, such as trifluoromethyl; cyano; nitro; halogen atoms; substituted or unsubstituted amino groups such as amino, diethylamino, and pyrrolidinyl (substituted amino groups refer to amino groups having one or two alkyl groups with 1 to 6 carbon atoms, amino groups having one or two alkyl groups with 1 to 6 carbon atoms, or amino groups where two substituted alkyl groups are bonded together to form an alkane diene with 2 to 8 carbon atoms. Unsubstituted amino groups are -NH2). It should be noted that, as the aforementioned polymerizable groups, examples include (meth)acryloyl group and (meth)acryloyloxy group.
[0078] Of the compounds (I), those represented by any one of the following formulas (I-1) to (I-8) are preferred.
[0079] [Chemical Formula 5]
[0080]
[0081] [In formulas (I-1) to (I-8),
[0082] B 1 ~B 30 Each of the following can be independently represented as a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the definitions of substituted and unsubstituted amino groups are as described above), a chlorine atom, or a trifluoromethyl group.
[0083] n1 to n4 represent integers from 0 to 3 independently.
[0084] When n1 is 2 or more, multiple B 2 They can be the same or different.
[0085] When n² is 2 or more, multiple B 6 They can be the same or different.
[0086] When n3 is 2 or more, multiple B 9 They can be the same or different.
[0087] When n4 is 2 or more, multiple B 14They can be the same or different.
[0088] The preferred anthraquinone pigment is the compound represented by formula (I-9).
[0089] [Chemical Formula 6]
[0090]
[0091] In formula (I-9),
[0092] R 1 ~R 8 Each can independently represent a hydrogen atom, -R x -NH2, -NHR x -NR x 2. -SR x Or halogen atoms.
[0093] R x This refers to an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0094] The preferred oxazine pigment is the compound represented by formula (I-10).
[0095] [Chemical Formula 7]
[0096]
[0097] In formula (I-10),
[0098] R 9 ~R 15 The hydrogen atom, -Rx, -NH2, and -NHR are represented independently of each other. x -NR x 2. -SR x Or halogen atoms.
[0099] R x This refers to an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0100] The preferred acridine dye is the compound represented by formula (I-11).
[0101] [Chemical Formula 8]
[0102]
[0103] In formula (I-11),
[0104] R 16 ~R 23 Each can independently represent a hydrogen atom, -R x -NH2, -NHR x -NRx 2. -SR x Or halogen atoms.
[0105] R x This refers to an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0106] In equations (I-9), (I-10), and (I-11), R is used as... x Alkyl groups having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, and hexyl, while aryl groups having 6 to 12 carbon atoms include phenyl, tolueneyl, xylyl, and naphthyl.
[0107] As the aforementioned anthocyanins, compounds represented by formula (I-12) and formula (I-13) are preferred.
[0108] [Chemical Formula 9]
[0109]
[0110] In formula (I-12),
[0111] D 1 and D 2 The groups represented by any one of formulas (I-12a) to (I-12d) are independent of each other.
[0112] [Chemical Formula 10]
[0113]
[0114] n5 represents an integer from 1 to 3.
[0115] [Chemical Formula 11]
[0116]
[0117] In formula (I-13),
[0118] D 3 and D 4 The groups represented by any one of the formulas (I-13a) to (I-13h) are independently represented.
[0119] [Chemical Formula 12]
[0120]
[0121] n6 represents an integer from 1 to 3.
[0122] The weight-average molecular weight of organic dichroic pigments is typically 300–2000, preferably 400–1000.
[0123] The polymeric liquid crystal composition of the present invention exhibits excellent performance in suppressing the light degradation of dichroic pigments in the polarizing film during polarization. Therefore, the effects of the present invention are particularly significant when using organic dichroic pigments that are weakly resistant to ultraviolet light and other light in sunlight and are prone to light degradation. Thus, the polymeric liquid crystal composition of the present invention is particularly advantageous when using organic dichroic pigments that are prone to light degradation.
[0124] Among the aforementioned organic dichroic pigments, azo pigments are suitable for fabricating polarizing films with excellent polarization performance due to their high linearity. Therefore, in one embodiment of the present invention, the organic dichroic pigment included in the polymerizable liquid crystal composition is preferably an azo pigment.
[0125] Furthermore, in relation to the sulfur-based antioxidants described later, the organic dichroic pigment preferably has an aromatic ring structure. In one embodiment of the present invention, for the polymerizable liquid crystal composition, an azo pigment having an aromatic ring structure is more preferably used as the organic dichroic pigment.
[0126] The content of the organic dichroic pigment in the polymeric liquid crystal composition of the present invention can be appropriately determined according to the type of organic dichroic pigment used, etc., and is preferably 0.1 to 50 parts by mass relative to 100 parts by mass of the polymeric liquid crystal compound, more preferably 0.1 to 20 parts by mass, and even more preferably 0.1 to 12 parts by mass. When the content of the organic dichroic pigment is within the above range, it is less likely to disturb the orientation of the polymeric liquid crystal compound, and a polarizing film with high orientation order can be obtained.
[0127] The polymerizable liquid crystal composition of the present invention comprises a sulfur-based antioxidant having an aromatic ring structure and a thiol or thioether structure. This sulfur-based antioxidant functions as a so-called secondary antioxidant, decomposing peroxides generated by free radicals through light irradiation. By including the sulfur-based antioxidant, the polymerizable liquid crystal composition of the present invention exhibits a high inhibitory effect on yellowing over time in the resulting polarizing film.
[0128] The mechanism by which a polarizing film with excellent yellowing suppression effect can be obtained from the polymeric liquid crystal composition of the present invention is speculated as follows. Specifically, in the above-mentioned polymeric liquid crystal composition, the sulfur-based antioxidant having an aromatic ring structure can exist in a more harmoniously mixed state in the liquid crystal state comprising the polymeric liquid crystal compound and the organic dichroic pigment, thus reducing the intermolecular distance between it and the organic dichroic pigment. Therefore, this sulfur-based antioxidant is more likely to function as an antioxidant, not only suppressing the photodegradation of the organic dichroic pigment but also functioning for a long time to decompose free radicals generated over time in the liquid crystal cured film. Based on the above mechanism, it is speculated that, in the present invention, when the organic dichroic pigment has an aromatic ring structure, a polarizing film with even better yellowing suppression effect can be obtained. Furthermore, generally speaking, by coordinating the organic dichroic pigments within a highly ordered polymeric liquid crystal compound, a polarizing film with excellent polarization performance can be obtained. When the sulfur-based antioxidant is structurally similar to the organic dichroic pigment, it can exist in the liquid crystal without disrupting the coordinated orientation brought about by the polymeric liquid crystal compound and the organic dichroic pigment. Thus, while maintaining the high degree of orientation order of the polymeric liquid crystal compound and the organic dichroic pigment, the photodegradation suppression effect of the organic dichroic pigment can be expected, thereby obtaining a polarizing film with excellent polarization performance.
[0129] Therefore, when the polymerizable liquid crystal composition contains a compound having an aromatic ring structure, such as an organic dichroic pigment having an aromatic ring structure as an example above, the more significant effects of the present invention are particularly expected.
[0130] Sulfur-based antioxidants (hereinafter also referred to as "sulfur-based antioxidants (S)") having aromatic ring structures, thiol structures, or thioether structures are not particularly limited. Sulfur-based antioxidants (S) can be used alone or in combination of two or more.
[0131] Examples of aromatic ring structures included in sulfur-based antioxidants (S) include aromatic hydrocarbon rings and heteroaromatic rings. Each of these aromatic ring structures can be a monocyclic structure or a fused ring structure. The aromatic ring structure is preferably a heteroaromatic ring, more preferably a heteroaromatic ring having at least one of nitrogen, sulfur, and oxygen, and even more preferably a heteroaromatic ring having at least one of nitrogen and sulfur. When the aromatic ring structure is a fused ring structure, it can be a fused ring formed by two rings or a fused ring formed by three or more rings. Examples of aromatic ring structures include benzene rings, naphthyl rings, quinoline rings, thiazole rings, benzothiazole rings, thienothiazole rings, imidazole rings, benzimidazole rings, oxazole rings, and benzoxazole rings. The hydrogen atoms contained in the aforementioned aromatic rings can be substituted. Examples of substituents include halogen atoms, alkyl groups having 1 to 4 carbon atoms, alkoxy groups having 1 to 4 carbon atoms, cyano groups, and nitro groups.
[0132] From the viewpoint of easily obtaining lightfastness and yellowing inhibition effect, as well as high polarization characteristics, sulfur-based antioxidants (S) preferably include at least one selected from the group consisting of thiols having aromatic rings, thioethers having aromatic rings, and cyclic thioethers having aromatic rings.
[0133] Examples of sulfur-based antioxidants (S) include compounds having the structure represented by formula (S1) and compounds having the structure represented by formula (S2).
[0134] [Chemical Formula 13]
[0135]
[0136] In formula (S1), m is 1 or 2, preferably 1.
[0137] In formula (S1), X is -N- or -CH-, and Y is -NH-, -N(Me)- (Me refers to methyl), -S-, -O-, -C(=O)-, -CH2-, or -CH=CH-. Preferably, at least one of X and Y contains at least one heteroatom as described above, more preferably X and Y each contain a heteroatom as described above, and even more preferably X is -N- and Y is -NH-.
[0138] In formula (S1), R1 is a hydrogen atom or a branched or unbranched alkyl group having 1 to 12 carbon atoms, preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, more preferably a hydrogen atom or a methyl group, and even more preferably a hydrogen atom.
[0139] In formula (S1), R2 to R5 are each independently a hydrogen atom, -OH, -NH2, a branched or unbranched alkyl group with 1 to 12 carbon atoms, a branched or unbranched alkoxy group with 1 to 12 carbon atoms, or a branched or unbranched thioalkyl group with 1 to 12 carbon atoms. Preferably, R2, R4, and R5 are all hydrogen atoms, and R3 is a hydrogen atom, -OH, -NH2, a branched or unbranched alkyl group with 1 to 12 carbon atoms, a branched or unbranched alkoxy group with 1 to 12 carbon atoms, or a branched or unbranched thioalkyl group with 1 to 12 carbon atoms. More preferably, R2 to R5 are all hydrogen atoms.
[0140] In formula (S2), n is 1 or 2, preferably 1.
[0141] The two benzene rings in formula (S2) can be bonded by a linking group Z. In formula (S2), --Z-- indicates that the linking group Z is any bond. Examples of linking groups Z include single bonds, -NH-, -N(Me)- (Me refers to methyl), -S-, -O-, -C(=O)-, -CH2-, etc. If the two benzene rings are not bonded by a linking group Z, their non-linking sites can each be independently a hydrogen atom, -NH2, -OH, -NO2, a branched or unbranched alkyl group with 1 to 12 carbon atoms, a branched or unbranched alkoxy group with 1 to 12 carbon atoms, or a branched or unbranched thioalkyl group with 1 to 12 carbon atoms.
[0142] In formula (S2), the two benzene rings are preferably bonded by a linking group Z, which is more preferably -NH-, -N(Me)-, -S- or -O-, and is even more preferably -NH- or -N(Me)-.
[0143] In formula (S2), R6~R 13 Each of the following is independently a hydrogen atom, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, a branched or unbranched alkoxy group having 1 to 12 carbon atoms, or a branched or unbranched thioalkyl group having 1 to 12 carbon atoms.
[0144] When the linking group Z is -NH-, R6, R8 to R1 are preferred. 11 and R 13 All are hydrogen atoms, and R7 and R 12 Each of the following is independently a hydrogen atom, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, a branched or unbranched alkoxy group having 1 to 12 carbon atoms, or a branched or unbranched thioalkyl group having 1 to 12 carbon atoms, and more preferably R7 is also a hydrogen atom.
[0145] When the linker group Z is -N(Me)-, R6, R8 to R1 are preferred. 11 and R 13All are hydrogen atoms, and R7 and R 12 Each of the following components is independently a hydrogen atom, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, a branched or unbranched alkoxy group having 1 to 12 carbon atoms, or a branched or unbranched thioalkyl group having 1 to 12 carbon atoms; more preferably, R7 is also a hydrogen atom; and even more preferably, R6 to R7 are also hydrogen atoms. 13 It consists entirely of hydrogen atoms.
[0146] Examples of compounds that are thiols having aromatic rings, thioethers having aromatic rings, and cyclic thioethers having aromatic rings include the following compounds.
[0147] [Chemical Formula 14]
[0148]
[0149] The weight-average molecular weight of the sulfur-based antioxidant (S) is preferably 600 or less, more preferably 400 or less, and even more preferably 250 or less. When the weight-average molecular weight is below the aforementioned upper limit, it is easy to orient in the liquid crystal molecules without disturbing the orientation of the polymerizable liquid crystal compound, and can exist near the organic dichroic pigment, thus further improving the light degradation inhibition effect of the organic dichroic pigment and the yellowing inhibition effect of the polarizing film. The weight-average molecular weight of the sulfur-based antioxidant (S) is not particularly limited, but is generally 50 or more, preferably 100 or more.
[0150] Among them, sulfur-based antioxidants, with their low steric hindrance and high linearity, tend to align with polymerizable liquid crystal compounds, exhibiting excellent photodegradation inhibition effects on organic dichroic pigments and yellowing inhibition effects on polarizing films, and are therefore preferred. The sulfur-based antioxidant (S) in this invention is preferably a sulfur compound with a benzimidazole ring, such as 2-mercaptobenzimidazole; a thiophenothiazine with substituents, such as 10-methylphenothiazine, 2-methoxyphenothiazine, or 2-ethylthiophenothiazine; and so on, but is not limited thereto.
[0151] The content of sulfur-based antioxidant (S) relative to 100 parts by mass of the polymerizable liquid crystal compound is preferably 0.1 to 3 parts by mass, more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, more preferably 2.5 parts by mass or less, and even more preferably 2 parts by mass or less. When the content of sulfur-based antioxidant (S) is at or above the aforementioned lower limit, it can effectively suppress the photodegradation of organic dichroic pigments and the yellowing of the obtained polarizing film. In addition, when the content of sulfur-based antioxidant (S) is below the aforementioned upper limit, it is less likely to disturb the orientation of the polymerizable liquid crystal compound, and a high suppression effect on the photodegradation of organic dichroic pigments and the yellowing of the obtained polarizing film can be expected.
[0152] Polymerizable liquid crystal compositions may also contain antioxidants other than sulfur-based antioxidants (S).
[0153] As antioxidants other than sulfur-based antioxidants (S), examples include secondary antioxidants such as sulfur-based antioxidants and phosphorus-based antioxidants that do not have an aromatic ring structure, as well as primary antioxidants such as phenolic antioxidants and amine antioxidants that have the function of capturing generated free radicals.
[0154] When the polymeric liquid crystal composition contains antioxidants other than sulfur-based antioxidants (S), from the viewpoint of maintaining a sufficiently high yellowing inhibition effect while maintaining the highly oriented order of the polymeric liquid crystal compound, the content of sulfur-based antioxidants (S) is preferably 50% by mass or more, more preferably 70% by mass or more, relative to the total amount of all antioxidants contained in the polymeric liquid crystal composition.
[0155] The polymerizable liquid crystal composition of the present invention may further include a polymerization initiator.
[0156] A polymerization initiator is a compound capable of initiating the polymerization reaction of a polymerizable liquid crystal compound. From the perspective of initiating the polymerization reaction at relatively low temperatures, photopolymerization initiators are preferred. Specifically, examples include photopolymerization initiators capable of generating active free radicals or acids under the influence of light, with photopolymerization initiators that generate free radicals under the influence of light being preferred. Polymerization initiators can be used alone or in combination of two or more.
[0157] Examples of polymerization initiators include benzoin compounds, benzophenone compounds, alkyl benzophenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and matte salts.
[0158] Examples of benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0159] Examples of benzophenone compounds include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0160] Examples of alkyl phenyl ketone compounds include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone, 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1,2-diphenyl-2,2-dimethoxy-1-ethyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 1-hydroxycyclohexylphenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]-1-propanone.
[0161] Examples of acylphosphine oxide compounds include 2,4,6-trimethylbenzoyl diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0162] Examples of triazine compounds include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethyl [Alkenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)vinyl]-1,3,5-triazine and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)vinyl]-1,3,5-triazine, etc.
[0163] Commercially available substances can be used as polymerization initiators. Commercially available polymerization initiators include, for example, "Irgacure (registered trademark) 907", "Irgacure (registered trademark) 184", "Irgacure (registered trademark) 651", "Irgacure (registered trademark) 819", "Irgacure (registered trademark) 250", "Irgacure (registered trademark) 369" (Ciba Japan Co., Ltd.); "SEIKUOL (registered trademark) BZ", "SEIKUOL (registered trademark) Z", "SEIKUOL (registered trademark) BEE" (Seiko Chemical Co., Ltd.); "kayacure (registered trademark) BP100" (Nippon Kayaku Co., Ltd.); "kayacure (registered trademark) UVI-6992" (DOW Corporation); "ADEKA OPTOMER SP-152", "ADEKA OPTOMERSP-170 (ADEKA Co., Ltd.); "TAZ-A", "TAZ-PP" (Siber Hegner Co., Ltd., Japan); and "TAZ-104" (Sanwa Chemical Co., Ltd.), etc.
[0164] When the polymerizable liquid crystal composition contains a polymerization initiator, its content can be appropriately determined according to the type and amount of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition. Preferably, it is 0.1 to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass. When the content of the polymerization initiator is within the above range, polymerization can be carried out without disturbing the orientation of the polymerizable liquid crystal compound.
[0165] When a polymerizable liquid crystal composition contains a photopolymerization initiator, it may also contain a photosensitizer. By using a photosensitizer, the polymerization reaction of the polymerizable liquid crystal compound can be further promoted.
[0166] Examples of photosensitizers include xanthonone compounds such as 2,4-diethylthioxanthonone and 2-isopropylthioxanthonone; anthracene compounds such as anthracene and alkoxy-containing anthracene (dibutoxyanthracene, etc.); phenothiazine and rubrene. Photosensitizers can be used alone or in combination of two or more.
[0167] The content of photosensitizer in the polymeric liquid crystal composition of the present invention can be appropriately determined according to the type and amount of photopolymerization initiator and polymeric liquid crystal compound. It is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of polymeric liquid crystal compound, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass.
[0168] The polymerizable liquid crystal composition of the present invention may further contain a leveling agent. The leveling agent has the function of adjusting the flowability of the polymerizable liquid crystal composition and making the coating obtained by coating the polymerizable liquid crystal composition smoother; specifically, surfactants are an example. Preferably, at least one is selected from the group consisting of leveling agents mainly composed of polyacrylate compounds and leveling agents mainly composed of compounds containing fluorine atoms.
[0169] Leveling agents can be used alone or in combination of two or more.
[0170] Examples of leveling agents with polyacrylate compounds as the main component include "BYK-350", "BYK-352", "BYK-353", "BYK-354", "BYK-355", "BYK-358N", "BYK-361N", "BYK-380", "BYK-381", and "BYK-392" (BYK Chemie).
[0171] Examples of leveling agents whose main component is a compound containing fluorine atoms include MEGAFACE (registered trademark) R-08, MEGAFACE R-30, MEGAFACE R-90, MEGAFACE F-410, MEGAFACE F-411, MEGAFACE F-443, MEGAFACE F-445, MEGAFACE F-470, MEGAFACE F-471, and MEGAFACE. E “F-477”, MEGAFACE “F-479”, MEGAFACE “F-482” and MEGAFACE “F-483” (DIC Corporation); “Surflon (registered trademark) S-381”, Surflon “S-382”, Surflon “S-383”, Surflon “S-393”, Surflon “SC-101”, Surflon “SC-105”, “KH-40” and “SA-100”
[0172] (AGC Seimi Chemical Co., Ltd.); "E1830", "E5844" (Daikin Fine ChemicalKenkyusho, KK); "EFTOP EF301", "EFTOP EF303", "EFTOP EF351" and "EFTOP EF352" (Mitsubishi Materials Electronic Chemicals Co., Ltd.), etc.
[0173] The leveling agent content in the polymeric liquid crystal composition of the present invention is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymeric liquid crystal compound.
[0174] When the leveling agent content is within the aforementioned range, it tends to: easily align the polymerizable liquid crystal compound horizontally, and is less prone to unevenness, resulting in a smoother polarizing film.
[0175] The polymerizable liquid crystal composition of the present invention may further include additives other than polymerization initiators, photosensitizers, and leveling agents. Examples of such additives include mold release agents, stabilizers, colorants such as bluing agents, flame retardants, and lubricants. When the polymerizable liquid crystal composition contains other additives, the content of these additives is preferably greater than 0% and less than 20% by mass, more preferably greater than 0% and less than 10% by mass, relative to the solid component of the polymerizable liquid crystal composition.
[0176] The polymerizable liquid crystal composition of the present invention may further comprise a solvent. For example, compounds exhibiting smectic liquid crystal properties typically have high viscosity; therefore, by adding a solvent to the polymerizable liquid crystal composition, coating becomes easier, and consequently, the formation of a polarizing film often becomes easier. The solvent can be appropriately selected based on the solubility of the polymerizable liquid crystal compound and the organic dichroic pigment. Examples include: alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl pentyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene; etc.
[0177] These solvents can be used alone or in combination of two or more. The solvent content is preferably 100 to 1900 parts by mass relative to 100 parts by mass of the solid component constituting the polymerizable liquid crystal composition, more preferably 150 to 900 parts by mass, and even more preferably 180 to 600 parts by mass.
[0178] The polymeric liquid crystal composition of the present invention is generally prepared by mixing and stirring a polymeric liquid crystal compound, an organic dichroic pigment and a sulfur-based antioxidant, as well as the above-mentioned additives and solvents added as needed.
[0179] The polymeric liquid crystal composition of the present invention can produce a liquid crystal cured film that is not prone to yellowing over time, and therefore can be suitable for use in the manufacture of polarizing films. Therefore, the present invention focuses on polarizing films formed from the cured film of the polymeric liquid crystal composition of the present invention.
[0180] The polymeric liquid crystal composition of the present invention enables the manufacture of polarizing films with high orientation order.
[0181] For polarizing films with high orientation order, Bragg peaks from higher-order structures such as hexatic phase and crystalline phase can be obtained in X-ray diffraction measurements.
[0182] The Bragg peak, also known as the molecular periodicity peak, refers to a peak originating from the planar periodic structure of molecular orientation. Therefore, in the polarizing film formed from the polymeric liquid crystal composition of the present invention, the polymeric liquid crystal compound or its polymer is preferably oriented in a manner that produces a Bragg peak in X-ray diffraction measurements, and more preferably in a "horizontal orientation" where the molecules of the polymeric liquid crystal compound are oriented along the direction of light absorption. In the present invention, the preferred planar periodicity of molecular orientation is... The polarizing film exhibits a high degree of orientational order, such as the Bragg peak, which can be achieved by controlling the type and amount of the polymeric liquid crystal compound used, the type and amount of the antioxidant, and the type and amount of the organic dichroic pigment.
[0183] The polarizing film of the present invention can be manufactured, for example, by a method including the following steps:
[0184] Forming a coating of the polymeric liquid crystal composition of the present invention;
[0185] Remove the solvent from the aforementioned coating;
[0186] After heating to a temperature above which the polymerizable liquid crystal compound transitions to a liquid phase, the temperature is then lowered to allow the polymerizable liquid crystal compound to transition to a liquid crystal phase (smectic liquid crystal state); and,
[0187] While maintaining the aforementioned liquid crystal phase (smectic liquid crystal state), the polymerizable liquid crystal compound is polymerized.
[0188] The formation of a coating film of a polymeric liquid crystal composition can be achieved by coating the polymeric liquid crystal composition, especially a polymeric liquid crystal composition whose viscosity has been adjusted by adding a solvent (hereinafter also referred to as "polarizing film forming composition"), onto a substrate, an alignment film described later, or the like. Alternatively, the polymeric liquid crystal composition can be directly coated onto the phase retardation film or other layers constituting the polarizing plate of the present invention.
[0189] The substrate is typically a transparent substrate. When the substrate is not disposed on the display surface of the display element, for example, when a laminate obtained by removing the substrate from the polarizing film is disposed on the display surface of the display element, the substrate may be opaque. A transparent substrate refers to a substrate that allows light, especially visible light, to pass through. Transparency refers to the characteristic that the transmittance of light in the wavelength range of 380–780 nm is 80% or more. Specific examples of transparent substrates include light-transmitting resin substrates. Examples of resins constituting light-transmitting resin substrates include: polyolefins such as polyethylene and polypropylene; cyclic olefin resins such as norbornene polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide; and polyphenylene ether. From the viewpoints of ease of acquisition and transparency, polyethylene terephthalate, polymethacrylate, cellulose ester, cyclic olefin resins, or polycarbonate are preferred. Cellulose esters are products obtained by esterification of some or all of the hydroxyl groups contained in cellulose, and are readily available from the market. Furthermore, cellulose ester substrates are also readily available from the market. Examples of commercially available cellulose ester substrates include "Fujitac Film" (Fujifilm Corporation); "KC8UX2M", "KC8UY", and "KC4UY" (KonicaMinolta Opto Products Co., Ltd.).
[0190] The required properties of the substrate vary depending on the composition of the polarizing film. Generally, a substrate with the smallest possible phase difference is preferred. Examples of substrates with the smallest possible phase difference include cellulose ester films such as ZeroTAC (Konica Minolta Opto, Inc.) and Z-TAC (Fujifilm Corporation), which do not have phase difference. Unstretched cyclic olefin resin substrates are also preferred. Hard coating, antireflective treatment, and antistatic treatment can be applied to the surface of the substrate where the polarizing film is not laminated.
[0191] When the substrate thickness is too thin, the strength decreases and the processability tends to be poor. Therefore, the thickness is usually 5 to 300 μm, preferably 20 to 200 μm, and more preferably 20 to 100 μm.
[0192] Methods for coating a polarizing film forming composition onto a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, applicator coating, and printing methods such as flexographic printing.
[0193] Next, under conditions where the polymerizable liquid crystal compound contained in the coating film obtained from the polarizing film forming composition does not polymerize, the solvent is removed by drying or the like, thereby forming a dried coating film. Examples of drying methods include natural drying, ventilation drying, heating drying, and reduced pressure drying.
[0194] Furthermore, in order to transform the polymeric liquid crystal compound into a liquid phase, the temperature is raised above the temperature at which the polymeric liquid crystal compound transforms into a liquid phase, and then cooled to transform the polymeric liquid crystal compound into a liquid crystal phase (smectic liquid crystal state). The phase transformation can be carried out after the solvent in the aforementioned coating is removed, or it can be carried out simultaneously with the removal of the solvent.
[0195] By polymerizing the polymeric liquid crystal compound while maintaining it in a liquid crystal phase (smectic liquid crystal state), a cured film of the polymeric liquid crystal composition is formed as a polarizing film. Photopolymerization is preferred as the polymerization method. In photopolymerization, the light irradiating the dried coating film can be appropriately selected based on the type of photopolymerization initiator contained in the dried coating film, the type of the polymeric liquid crystal compound (especially the type of polymeric groups possessed by the polymeric liquid crystal compound), and their amount. Specific examples include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, and gamma rays, and active electron beams. Ultraviolet light is preferred from the perspective of easy control of the polymerization reaction and the use of apparatus widely used in the art as photopolymerization devices. It is also preferable to pre-select the type of polymeric liquid crystal compound and photopolymerization initiator contained in the polymeric liquid crystal composition in a manner that photopolymerization can be carried out by ultraviolet light. Furthermore, during polymerization, the polymerization temperature can be controlled by irradiating the dried coating film while simultaneously cooling it with appropriate cooling methods. By employing such a cooling method, the polymerization of polymerizable liquid crystal compounds can be carried out at a lower temperature, allowing for the appropriate formation of a polarizing film even when a substrate with low heat resistance is used. During photopolymerization, patterned polarizing films can also be obtained through masking, development, and other processes.
[0196] Examples of light sources for the aforementioned active energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380–440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.
[0197] Ultraviolet radiation intensity is typically 10–3,000 mW / cm². 2The intensity of ultraviolet irradiation is preferably within the wavelength range effective for activating the photopolymerization initiator. The irradiation time is typically 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and even more preferably 10 seconds to 1 minute. When irradiated once or multiple times at this intensity, the cumulative light intensity is 10 to 3,000 mJ / cm². 2 Preferably, it is 50–2,000 mJ / cm². 2 More preferably 100–1,000 mJ / cm 2 .
[0198] Photopolymerization is performed on polymerizable liquid crystal compounds in a liquid crystal state that retains the liquid crystal phase, preferably the smectic phase, and more preferably a higher-order smectic phase, to form a polarizing film. Polarizing films obtained by polymerizing polymerizable liquid crystal compounds in a smectic liquid crystal state also benefit from the aforementioned dichroic pigment effect, offering advantages such as higher polarization performance compared to conventional host-guest type polarizing films, i.e., polarizing films formed from the nematic liquid crystal state. Furthermore, compared to films formed by coating only with dichroic pigments and lyotropic liquid crystals, they also exhibit superior strength.
[0199] The thickness of the polarizing film can be appropriately selected according to the applicable display device, preferably 0.5 to 4 μm, more preferably 0.5 to 3 μm.
[0200] The polarizing film is preferably formed on an alignment film. This alignment film is a film having an alignment limiting force that aligns the polymeric liquid crystal compound in a desired direction. As an alignment film, it is preferable to have solvent resistance that prevents dissolution due to coating of the composition containing the polymeric liquid crystal compound, and heat resistance to heat treatments used for solvent removal and alignment of the polymeric liquid crystal compound. Examples of such alignment films include alignment films containing an alignment polymer, photoalignment films, groove alignment films with a surface pattern or multiple grooves, and stretched films stretched along the alignment direction. From the viewpoint of accuracy and quality of the alignment angle, a photoalignment film is preferred.
[0201] Examples of oriented polymers include polyamides with intramolecular amide bonds, gelatin-like polymers, polyimides with intramolecular imide bonds and their hydrolysates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylates. Polyvinyl alcohol is preferred.
[0202] Oriented polymers can be used alone or in combination of two or more.
[0203] Oriented films containing oriented polymers can typically be obtained by coating a substrate with a composition (hereinafter sometimes referred to as "oriented polymer composition") formed by dissolving the oriented polymer in a solvent, and then removing the solvent; or by coating the substrate with the oriented polymer composition, removing the solvent, and then rubbing (rubbing method). As a solvent, the same solvents exemplified above as those used in forming polarizing films can be considered.
[0204] Regarding the concentration of the oriented polymer in the oriented polymer composition, it is acceptable as long as the oriented polymer material can be completely dissolved in the solvent. Relative to the solution, in terms of solid content, it is preferably 0.1 to 20%, and more preferably about 0.1 to 10%.
[0205] As an orientation polymer composition, commercially available orientation film materials can be used directly. Examples of commercially available orientation film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and OPTOMER (registered trademark, manufactured by JSR Corporation).
[0206] As a method for coating an oriented polymer composition onto a substrate, the same method as that exemplified as a method for coating a polarizing film forming composition onto a substrate can be described.
[0207] Methods for removing solvents contained in oriented polymer compositions include natural drying, ventilation drying, heating drying, and vacuum drying.
[0208] To impart orientation-restricting forces to the alignment film, a friction treatment (friction method) may be performed as needed.
[0209] As a method of imparting orientation-restricting force by friction, an example is a method of contacting a friction roller that is wound with friction cloth and rotated with a film of an orientation polymer formed on the surface of a substrate by coating an orientation polymer composition onto a substrate and annealing it.
[0210] Photoalignment films are typically obtained by coating a composition (hereinafter also referred to as "photoalignment film forming composition") containing a polymer or monomer having photoreactive groups and a solvent onto a substrate and irradiating it with polarized light (preferably polarized UV light). Photoalignment films are more preferably preferred from the viewpoint that the direction of the alignment restraint force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0211] A photoreactive group refers to a group that generates liquid crystal orientation ability through light irradiation. Specifically, it includes photoreactive groups that participate in molecular orientation-inducing or isomerization reactions, dimerization reactions, photocrosslinking reactions, or photodecomposition reactions that occur through light irradiation, thus becoming the origin of liquid crystal orientation ability. Among these, groups participating in dimerization reactions or photocrosslinking reactions are preferred from the perspective of excellent orientation. As a photoreactive group, it is preferred to have a group having unsaturated bonds, especially double bonds, and particularly preferred to have a group having at least one of the following: carbon-carbon double bonds (C=C bond), carbon-nitrogen double bonds (C=N bond), nitrogen-nitrogen double bonds (N=N bond), and carbon-oxygen double bonds (C=O bond).
[0212] Examples of photoreactive groups with C=C bonds include vinyl, polyene, styrene, styrenezolium, styrenezolium, chalcone, and cinnamoyl.
[0213] Examples of photoreactive groups with C=N bonds include those with aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups with N=N bonds include azophenyl, azonaphthyl, aromatic heterocyclic azo, diazo, and methyl groups. The group includes alkyl groups and groups having an azobenzene structure. Examples of photoreactive groups with C=O bonds include benzophenone, coumarin, anthraquinone, and maleimide. These groups may have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and haloalkyl.
[0214] Among these, photoreactive groups that participate in the photodimerization reaction are preferred. Considering that the amount of polarized light required for photoorientation is relatively small and that photoorientation films with excellent thermal stability and long-term stability are easily obtained, cinnamyl and chalcone groups are preferred. As polymers with photoreactive groups, polymers with cinnamyl groups at the ends of their side chains, forming a cinnamic acid structure, are particularly preferred.
[0215] By coating a composition for forming a photo-alignment film onto a substrate, a photo-alignment induction layer can be formed on the substrate. As a solvent included in the composition, the same solvents exemplified above as those used in forming a polarizing film can be appropriately selected based on the solubility of the polymer or monomer having photoreactive groups.
[0216] The content of the polymer or monomer with photoreactive groups in the composition for forming a photoalignment film can be appropriately adjusted according to the type of polymer or monomer and the thickness of the target photoalignment film. It is preferably at least 0.2% by mass, more preferably in the range of 0.3% to 10% by mass, relative to the mass of the composition for forming the photoalignment film. The composition for forming the photoalignment film may contain polymers such as polyvinyl alcohol and polyimide, and photosensitizers, within a range that does not significantly impair the properties of the photoalignment film.
[0217] As a method for coating a composition for forming a photo-alignment film onto a substrate, the same method as the method for coating an orientation composition onto a substrate can be cited. As a method for removing solvent from the coated composition for forming a photo-alignment film, examples include natural drying, ventilation drying, heating drying, and reduced pressure drying.
[0218] For irradiating with polarized light, the method can be either direct irradiation of polarized UV light onto the product obtained by removing the solvent from the composition for forming a photo-alignment film coated on a substrate, or irradiation from the substrate side, allowing the polarized light to pass through. This polarized light is particularly preferably substantially parallel light. The wavelength of the irradiated polarized light should be within the wavelength range where the photoreactive groups of the polymer or monomer having photoreactive groups can absorb light energy. Specifically, UV (ultraviolet) light in the wavelength range of 250–400 nm is particularly preferred. Examples of light sources for this polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, and other ultraviolet lasers, with high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps being more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferred due to the high luminous intensity of ultraviolet light at a wavelength of 313 nm. By passing light from the above-mentioned light sources through a suitable polarizer, polarized UV light can be irradiated.
[0219] As the polarizer, polarizing filters, Glan-Thompson polarizers, Glan-Taylor polarizers, and wire grid polarizers can be used.
[0220] It should be noted that if masking is performed during rubbing or polarized light irradiation, multiple regions (patterns) with different liquid crystal orientations can also be formed.
[0221] A groove-aligned film is a film with raised or recessed patterns or multiple grooves on its surface. When a polymerizable liquid crystal compound is coated onto a film having multiple linearly arranged grooves at equal intervals, the liquid crystal molecules are aligned along the direction of the grooves.
[0222] Methods for obtaining grooved oriented films include: exposing the surface of a photosensitive polyimide film through an exposure mask with a patterned slit, followed by development and rinsing to form a raised or recessed pattern; forming a layer of UV-curable resin before curing on a plate-shaped master with grooves on its surface, transferring the formed resin layer to a substrate, and then curing it; and pressing a roller-shaped master with multiple grooves onto a film of UV-curable resin before curing formed on a substrate to form a raised or recessed pattern, and then curing it; and so on.
[0223] The thickness of the alignment film (an alignment film containing an alignment polymer or a photoalignment film) is typically in the range of 10 to 10,000 nm, preferably in the range of 10 to 1,000 nm, more preferably below 500 nm, even more preferably in the range of 10 to 200 nm, and particularly preferably in the range of 50 to 150 nm.
[0224] This invention comprises a polarizing film comprising the polarizing film and a transparent film of this invention. The transparent film, as referred to herein, is a film that is transparent enough to transmit light, especially visible light; transparency is defined as a transmittance of 80% or more for light in the wavelength range of 380–780 nm. In the polarizing film of this invention, the transparent film may be, for example, a transparent substrate as described above, or it may be a protective film for protecting the polarizing film. In the polarizing film of this invention, the transparent film may be laminated on only one side of the polarizing film or on both sides. When the polarizing film of this invention comprises multiple transparent films, they may be identical or different from each other. Furthermore, the polarizing film and the transparent film may be in contact with each other or separated. Typically, the transparent film may be bonded to the polarizing film via an adhesive layer or a bonding agent layer.
[0225] Furthermore, the present invention includes a circular polarizer comprising the polarizing film and the retardation film of the present invention. In the circular polarizer of the present invention, the retardation film preferably satisfies formulas (1) and (2). It should be noted that, in cases where the retardation film is composed of a liquid crystal curing layer formed on a substrate film or other layers other than the layer presenting the phase difference (retardation presentation layer), the retardation presentation layer preferably satisfies the optical properties expressed by formulas (1) and (2).
[0226] 100nm≤Re(550)≤150nm (1)
[0227] Re(450) / Re(550)<1 (2)
[0228] [In the formula, Re(λ) represents the frontal phase difference of light relative to wavelength λnm.]
[0229] When the phase difference film has the frontal phase difference value represented by (1) above, it functions as a so-called λ / 4 plate. The aforementioned formula (1) is preferably 120nm≤Re(550)≤150nm.
[0230] The phase difference film that satisfies the above equation (2) has so-called inverse wavelength dispersion and exhibits excellent polarization performance. The value of Re(450) / Re(550) is preferably 0.93 or less, more preferably 0.88 or less, even more preferably 0.86 or less, more preferably 0.80 or more, and more preferably 0.82 or more.
[0231] The aforementioned frontal phase difference value can be adjusted by the film thickness dA of the phase difference film (phase difference rendering layer). The frontal phase difference value is determined by the formula Re(λ)=(nx(λ)-ny(λ))×dA [dA represents the thickness of the phase difference film (phase difference rendering layer), nx represents the principal refractive index at wavelength λnm in the direction parallel to the plane of the phase difference film in the refractive index ellipsoid formed by the phase difference film, and ny represents the refractive index at wavelength λnm in the direction parallel to the plane of the phase difference film and orthogonal to the aforementioned nx direction in the refractive index ellipsoid formed by the phase difference film]. Therefore, in order to obtain the desired frontal phase difference value (Re(λ): in-plane phase difference value of the phase difference layer at wavelength λ(nm), the three-dimensional refractive index and film thickness dA can be adjusted.
[0232] The aforementioned retardation film can be a stretched film that imparts a phase difference by stretching a polymer. From the viewpoint of thinning the circular polarizer, it is preferable to be a cured product of a polymeric liquid crystal composition containing a polymeric liquid crystal compound, and to be composed of a polymer in the oriented state of the aforementioned polymeric liquid crystal compound. The retardation film constituting the circular polarizer of the present invention can be manufactured by appropriately selecting and employing materials and methods conventionally known in the art. As the polymeric liquid crystal compound forming the retardation film, for example, liquid crystal compounds described in Japanese Patent Application Laid-Open No. 2011-207765 can be used.
[0233] The thickness of the phase retardation film can be appropriately selected according to the display device to which it is applied. From the viewpoint of thin film and flexibility, it is preferably 0.1 to 10 μm, more preferably 1 to 5 μm, and even more preferably 1 to 3 μm.
[0234] The circular polarizer of the present invention comprises the polarizing film or polarizing sheet of the present invention and a phase retardation film, and may further include other layers (protective layer, adhesive layer, etc.). In the circular polarizer of the present invention, the polarizing film or polarizing sheet of the present invention and the phase retardation film may be bonded together through an adhesive layer or a bonding agent layer. Furthermore, in the circular polarizer of the present invention, the phase retardation film can be directly formed on the polarizing film of the present invention by directly coating the phase retardation film forming composition onto the polarizing film of the present invention.
[0235] In the circular polarizer of the present invention, the angle between the slow axis of the phase difference film and the absorption axis of the polarizer film is preferably substantially 45°. It should be noted that, in the present invention, "substantially 45°" means 45° ± 5°.
[0236] From the viewpoint of the flexibility and visual recognizability of the display device, the thickness of the circular polarizer of the present invention is preferably 10 to 300 μm, more preferably 20 to 200 μm, and even more preferably 25 to 100 μm.
[0237] The present invention includes a display device comprising the polarizing film of the present invention or the circular polarizing plate of the present invention.
[0238] The display device of the present invention can be obtained, for example, by attaching the polarizing film or circular polarizing plate of the present invention to the surface of the display device through an adhesive layer.
[0239] A display device is a device with a display mechanism that includes a light-emitting element or light-emitting device as a light source. Examples of display devices include liquid crystal displays, organic electroluminescent (EL) displays, inorganic electroluminescent (EL) displays, touch panel displays, electron emission displays (field emission displays (FED, etc.), surface conduction electron emission displays (SED)), electronic paper (display devices using electronic ink or electrophoretic elements), plasma displays, projection displays (grating light valve (GLV) displays, displays with digital micromirror devices (DMD), etc.), and piezoelectric ceramic displays, etc.
[0240] Liquid crystal display devices also include any of the following: transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, direct-viewing liquid crystal display devices, and projection liquid crystal display devices. These display devices can be display devices for displaying two-dimensional images or stereoscopic display devices for displaying three-dimensional images. In particular, as display devices of the present invention, organic EL display devices and touch panel display devices are preferred, with organic EL display devices being especially preferred.
[0241] Example
[0242] The present invention will be described in more detail below through examples and comparative examples. Unless otherwise specified, "%" and "parts" in the examples and comparative examples refer to "% by mass" and "parts by mass".
[0243] Comparative Example 1
[0244] The following components were mixed and stirred at 80°C for 1 hour to obtain a polymeric liquid crystal composition (1). The polymeric liquid crystal compound and the dichroic pigment used were those described in the examples of Japanese Patent Application Publication No. 2013-101328.
[0245] Polymerizable liquid crystal compounds:
[0246] [Chemical Formula 15]
[0247]
[0248] [Chemical Formula 16]
[0249]
[0250]
[0251] • Dichroic pigments:
[0252] Azo dyes;
[0253] [Chemical Formula 17]
[0254]
[0255] [Chemical Formula 18]
[0256]
[0257] [Chemical Formula 19]
[0258]
[0259] • Polymerization initiator:
[0260] 6 parts of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (Irgacure 369; manufactured by Ciba Specialty Chemicals Co., Ltd.)
[0261] Leveling agent:
[0262] 1.2 parts of polyacrylate compound (BYK-361N; manufactured by BYK-Chemie).
[0263] Solvent:
[0264] 400 parts of o-xylene
[0265] Furthermore, according to Table 1, 1 part of the antioxidant described below is mixed with 100 parts by mass of the polymeric liquid crystal composition (1), and otherwise the same procedure is performed as with the polymeric liquid crystal composition (1) to obtain polymeric liquid crystal compositions (2) to (10).
[0266] Examples 1-4 and Comparative Examples 2-6
[0267] In the polymeric liquid crystal composition (1), in addition to the above-mentioned components, 1 part by mass of the following antioxidant was mixed. Otherwise, the polymeric liquid crystal compositions (polymeric liquid crystal compositions (2) to (10)) of Examples 1 to 4 and Comparative Examples 2 to 6 were prepared using the same method as Comparative Example 1.
[0268] [Chemical Formula 20]
[0269]
[0270] (Antioxidant A: 2-Mercaptobenzimidazole)
[0271] For use in polymeric liquid crystal compositions (2).
[0272] [Chemical Formula 21]
[0273]
[0274] (Antioxidant B: 10-methylphenthiazide)
[0275] For use in polymeric liquid crystal compositions (3).
[0276] [Chemical Formula 22]
[0277]
[0278] (Antioxidant C: 2-Methoxyphenthiazide)
[0279] For use in polymeric liquid crystal compositions (4).
[0280] [Chemical Formula 23]
[0281]
[0282] (Antioxidant D: 2-Ethiophenthiazine)
[0283] For use in polymeric liquid crystal compositions (5).
[0284] [Chemical Formula 24]
[0285]
[0286] (Antioxidant E: 4-Butoxy-4'-Hydroxybiphenyl)
[0287] For use in polymeric liquid crystal compositions (6).
[0288] [Chemical Formula 25]
[0289]
[0290] (Antioxidant F: 4-ethoxy-4'-hydroxybiphenyl)
[0291] Used in polymeric liquid crystal compositions (7).
[0292] [Chemical Formula 26]
[0293] (H 25 C 12 OCOCH2CH2)2S
[0294] (Antioxidant G: Sumilizer TPL, manufactured by Sumitomo Chemical Co., Ltd.)
[0295] For use in polymeric liquid crystal compositions (8).
[0296] [Chemical Formula 27]
[0297]
[0298] (Antioxidant H: Sumilizer TP-D, manufactured by Sumitomo Chemical Co., Ltd.)
[0299] For use in polymeric liquid crystal compositions (9).
[0300] [Chemical Formula 28]
[0301]
[0302] (Antioxidant I: DTDPA)
[0303] For use in polymeric liquid crystal compositions (10).
[0304] Furthermore, using the following steps, polarizing films of Examples 1 to 4 and Comparative Examples 1 to 6 were prepared using polymeric liquid crystal compositions (1) to (10).
[0305] (1) Fabrication of photo-aligned film on substrate
[0306] (i) Preparation of compositions for photo-alignment film formation
[0307] The following components as disclosed in Japanese Patent Application Publication No. 2013-033249 are mixed, and the resulting mixture is stirred at 80°C for 1 hour to obtain a composition for photo-alignment film formation.
[0308] • Photooriented polymers:
[0309] [Chemical Formula 29]
[0310]
[0311] 2 copies
[0312] Solvent:
[0313] 98 parts of o-xylene
[0314] (ii) Formation of photo-alignment film
[0315] As a transparent substrate, a triacetyl cellulose film (KC8UX2M, manufactured by KONICA MINOLTA Co., Ltd.) was used. After corona treatment of the film surface, the above-mentioned composition for forming a photo-aligned film was coated on it and dried at 120°C to obtain a dried film. Polarized UV light was irradiated onto the dried film to form a photo-aligned film, resulting in a film with the photo-aligned film. The polarized UV light treatment was performed using a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Electric Co., Ltd.) under conditions of an intensity of 100 mJ measured at a wavelength of 365 nm.
[0316] (2) Fabrication of polarizing film
[0317] On the thin film with the photo-alignment film obtained in the aforementioned manner, a polymeric liquid crystal composition (2) was coated using a rod coating method (#930mm / s). The film was then heated and dried in a drying oven at 120°C for 1 minute, thereby causing the polymeric liquid crystal compound to change to a liquid phase. After cooling to room temperature, the polymeric liquid crystal compound was transformed into a smectic liquid crystal state. Next, the layer formed from the polymeric liquid crystal composition was irradiated with a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Electric Co., Ltd.) at an exposure dose of 1000 mJ / cm². 2 Ultraviolet light (365nm reference) is used to polymerize the polymerizable liquid crystal compound contained in the dried film while maintaining its smectic liquid crystal state. This dried film forms a polarizing film, resulting in a polarizing film sheet with a transparent substrate, a photoalignment film, and a polarizing film sequentially stacked. The thickness of the polarizing film at this point was measured using a laser microscope (Olympus OLS3000), and the result was 2.3 μm.
[0318] For this polarizing film, X-ray diffraction measurements were performed using an X'Pert PRO MPD (manufactured by Spectris Co., Ltd.), and a sharp diffraction peak (Bragg peak) with a half-width at half-maximum (FWHM) of approximately 0.17° was obtained near 2θ = 20.2°.
[0319] Furthermore, the same result is obtained when incident from the direction perpendicular to the friction. The ordered period (d) obtained from the peak position is approximately It was confirmed that a structure reflecting a higher-order smectic phase was formed.
[0320] (3) Fabrication of laminated bodies
[0321] Furthermore, the surface of the polarizing film obtained above was subjected to corona treatment. Then, on the corona-treated surface, an aqueous solution (viscosity: 92 cP) was coated using a wire bar coater (#30) containing 7 parts of carboxyl-modified polyvinyl alcohol (Kuraray POVAL KL318 manufactured by KURARAY Co., Ltd.) and 3.5 parts of water-soluble polyamide epoxy resin (Sumirez Resin 650 obtained by Sumika Chemtex Co., Ltd., an aqueous solution with a solid component concentration of 30% by mass) as a thermal crosslinking agent. The aqueous solution was dried at 80°C for 5 minutes to form a protective layer, thus producing a polarizing film with a protective layer. Furthermore, glass (Corning Co., Ltd., Eagle XG) was bonded to the protective layer via an adhesive layer formed by a pressure-sensitive adhesive (Lintec Corporation, film thickness 25 μm) to obtain a laminate.
[0322] <Determination of polarization Py>
[0323] The polarization Py of the laminate was measured as follows. Using a spectrophotometer (Shimadzu Corporation UV-3150) with a folder equipped with a polarizer, the transmittance (Ta) along the transmission axis and the transmittance (Tb) along the absorption axis were measured in the wavelength range of 380–780 nm using a double-beam method. A screen that intercepts 50% of the light was placed on the reference side of the folder.
[0324] The polarization at each wavelength is calculated according to Equation 1 below. Then, visibility correction is performed using the 2-degree field of view (C light source) of JIS Z 8701 to calculate the visibility-corrected polarization (Py).
[0325] Polarization degree Py (%)=(Ta-Tb) / (Ta+Tb)×100 (Formula 1)
[0326] <Measurement of absorbance in the direction of transmission>
[0327] Using the same method as described above, and employing a device consisting of a folder with a polarizer mounted on a spectrophotometer (Shimadzu Corporation UV-3150), the absorbance (A1) in the transmission axis direction was measured using the double-beam method.
[0328] <Evaluation of lightfastness>
[0329] The lightfastness of the laminates of Examples 1-4 and Comparative Examples 1-6 was evaluated according to the following method. The results are shown in Table 1.
[0330] The triacetyl cellulose film, serving as the substrate of the above-mentioned laminate, was placed face up in a lightfastness testing machine (SUNTEST XLS+; manufactured by ATLAS) at a cumulative light intensity of 96120 KJ / m². 2 After irradiation under certain conditions, the polarization Py and absorbance A1 of the laminate were measured again. The rate of change of polarization Py ΔPy before and after the lightfastness test, and the change of absorbance at 420 nm as the yellowing inhibition benchmark were calculated and evaluated according to the following benchmarks.
[0331] <Evaluation Criteria>
[0332] Polarization change
[0333] A: The absolute value of the change in polarization |ΔPy| is less than 0.8.
[0334] B: The absolute value of the change in polarization, |ΔPy|, is greater than 0.8 and less than 1.2.
[0335] C: The absolute value of the change in polarization |ΔPy| is greater than 1.2.
[0336] Absorbance change
[0337] A: The absorbance change along the transmission axis is greater than 0% and less than 5%.
[0338] B: The absorbance variation along the transmission axis is greater than 5% but less than 10%.
[0339] C: Absorbance variation along the transmission axis is greater than 10%.
[0340] [Table 1]
[0341]
[0342] The polarizing films of Examples 1-4 obtained good results in each evaluation.
Claims
1. A polymerizable liquid crystal composition comprising a polymerizable liquid crystal compound, an organic dichroic pigment, and a sulfur-based antioxidant. The polymerizable liquid crystal compound has at least one free radical polymerizable group. The polymerizable liquid crystal compound is a liquid crystal compound exhibiting high-order smectic liquid crystal properties. The organic dichroic pigment has an aromatic ring structure. The sulfur-based antioxidants have aromatic ring structures, thiols, or thioether structures.
2. The polymerizable liquid crystal composition according to claim 1, wherein, Sulfur-based antioxidants are selected from at least one group consisting of thiols having aromatic rings, thioethers having aromatic rings, and cyclic thioethers having aromatic rings.
3. The polymerizable liquid crystal composition according to claim 1 or 2, wherein, Organic dichroic pigments are azo pigments.
4. The polymerizable liquid crystal composition according to claim 1 or 2, wherein, The content of sulfur-based antioxidants is 0.1 to 3 parts by mass relative to 100 parts by mass of polymeric liquid crystal compound.
5. A polarizing film formed from a cured film of the polymeric liquid crystal composition according to claim 1 or 2.
6. The polarizing film as described in claim 5, which exhibits a Bragg peak in X-ray diffraction measurements.
7. The polarizing film as described in claim 5 or 6, wherein the film thickness is in the range of 0.5 to 4 μm.
8. A polarizing film comprising the polarizing film and the transparent film as described in any one of claims 5 to 7.
9. A circular polarizing plate comprising a polarizing film and a phase difference film as described in any one of claims 5 to 7.
10. The circular polarizing plate as described in claim 9, wherein, The phase difference thin film satisfies equations (1) and (2): 100nm≤Re(550)≤150nm (1) Re(450) / Re(550)<1(2) In the formula, Re(λ) represents the frontal phase difference of light relative to wavelength λnm.
11. A display device comprising a polarizing film according to any one of claims 5 to 7, a polarizing film sheet according to claim 8, or a circular polarizing plate according to claim 9 or 10.
Citation Information
Patent Citations
JP1972019156U
Compound, optical film and method for producing optical film
JP2011207765A
Polarization element, circularly polarizing plate and method of manufacturing those
JP2013033249A
Polarizing film, circularly polarizing plate and their manufacturing method
JP2013101328A
Reinforcing-bar management system
JP2019008683A